All Days 2001
DOI: 10.2118/68335-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study to Evaluate Water Vaporisation and Formation Damage Caused by Dry Gas Flow through Porous Media

Abstract: Experiments were conducted to evaluate the rate of water vaporisation and the consequent permeability reduction caused by the flow of dry gas through porous media. Two sets of porous media were studied: unconsolidated Ottawa sandpacks and consolidated Berea cores, as well as various salinity brines ranging from 0 to 150 g/litre of NaCl. The experiments were conducted at an initial water saturation of about 14% for sandpacks and 24.6% for Berea cores. Tests indicate that the rate of water vaporisation increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 4 publications
0
18
1
Order By: Relevance
“…Bacci et al (2011) reported porosity changes between 4% and 29% of the estimated initial porosity. Permeability reduction between 0% and 86% of the estimated initial permeability from sandstone core flooding experiments have also been reported (Bacci et al, 2011;Wanga et al, 2009;Zuluaga et al, 2003;Zuluaga et al, 2001).…”
Section: Introductionmentioning
confidence: 61%
“…Bacci et al (2011) reported porosity changes between 4% and 29% of the estimated initial porosity. Permeability reduction between 0% and 86% of the estimated initial permeability from sandstone core flooding experiments have also been reported (Bacci et al, 2011;Wanga et al, 2009;Zuluaga et al, 2003;Zuluaga et al, 2001).…”
Section: Introductionmentioning
confidence: 61%
“…This claim has however been disproved by many studies including this present study 1,[3][4][5][6][7][8][9][10][11][12] . The falling rate period and the receding rate period are often combined together as stage-2 evaporation 6,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…11 Because the salinity of the deep formation water is commonly high, the solid salt precipitation is likely to occur near the injection well, which may dramatically alter formation porosity, permeability and injectivity. [12][13][14][15][16][17][18][19] To date, some models and experiments have been conducted to investigate salt precipitation and its effect on the injectivity. 13,[20][21][22][23][24][25][26] Pruess and Muller 9 set up isothermal one-dimensional and two-dimensional numerical models to investigate the salt precipitation process and influencing factors.…”
Section: Introductionmentioning
confidence: 99%